Capacity to consent to biomedical research’s evaluation among older cognitively impaired patients. A study to validate the University of California Brief Assessment of Capacity to Consent questionnaire in French among older cognitively impaired patients - Duron, Emmanuelle; Boulay, M; Vidal, Jean-Sébastien; El Bchiri, Jamila; Fraisse, Marie-Laure; Rigaud, Anne Sophie; Hugonot-Diener, Laurence (The Journal of nutrition, health & aging, 2013)
CONTEXT: Some studies have highlighted the difficulty for physicians to evaluate patient’s ability to consent to bio-medical research in the elderly population. The University of California Brief Assessment of Capacity to Consent (UBACC) is a rapid questionnaire to assess the ability to consent, previously validated among schizophrenic patients. OBJECTIVE: To evaluate the accuracy of the UBACC scale, French version, to determine the capacity to consent to biomedical studies of older people with normal cognition, mild cognitive impairment (MCI) or Alzheimer Disease (AD). DESIGN: A prospective validation study between September 2008 to November 2011. SETTING: A Memory clinic. PATIENTS: We included 61 subjects in a memory clinic who had already consented to participate to a biomedical research and had signed a consent form. Those subjects, who had memory impairment, had a comprehensive neuro-psychological (including Mini Mental State Examination (MMSE)/30), clinical, biological assessment and brain imagery during day-care hospital. They were classified as MCI or AD patients. Control group included patients’ caregivers without memory complaints and a normal comprehensive neuro-psychological assessment. INTERVENTION AND MEASUREMENTS: The consent form was once again explained to the subjects by a physician who subjectively evaluated if subjects had understood the study. Then, the 10 questions of the French version of the UBACC scale (max score 20) were asked to the participants. This scale evaluates the understanding of the study’s aim, risks and benefits. A comparison was made between subjective assessment and the UBACC score. RESULTS: The physician considered that 18/61 patients (2 MCI and 16 AD) had not understood. These ones had a lower UBACC score (Score/20 (SD) [range]: 7.56 (3.03) [0–12] versus 17.72 (2.68) [13–28], p<0.001), a lower MMSE (Score/30 (SD): 21.1 (5.9) versus 27.3 (2.9); p<0.001) and were older (age (years old) 80.8 versus 76.6. p<0.0001) compared to those who had understood. Moreover, all the patients who had not understood had an UBACC score ≤ 12. The administration time was accurate in this population (<10 minutes). CONCLUSION: The UBACC scale, in its French version, was accurate to assess capacity to consent in an older, cognitively impaired population.